PITUTUR LUHUR UNTUK PEMBERANTASAN KORUPSI DI INDONESIA DALAM PERSPEKTIF KEBIJAKAN HUKUM PIDANA - Moch. Choirul Rizal; M. Lutfi Rizal Farid (Refleksi Hukum: Jurnal Ilmu Hukum, 2017)
The study of this idea has a focus on “pitutur luhur” for eradicating corruption in Indonesia. The writing of this idea uses a penal policy approach. It is found that the eradication of corruption has not found significant success. One indicator is the Indonesian Corruption Perceptions Index that has not improved. Apparently, the excessive action taken by the KPK does not reduce the level of corruption much. In this regard, an action plan which is presumed to be worth "fighting" optimally is the eradication of corruption in a preventive manner, without then reducing any repressive efforts. Take, for example, revitalizing the “pitutur luhur” which is one of the local wisdom of Javanese culture. In the perspective of penal policy, efforts to make “pitutur luhur” for eradication of corruption in Indonesia can be interpreted as a manifestation of strategic efforts to improve social conditions that led to the birth of corrupt practices. Therefore, the concrete “pitutur luhur” effort to eradicate corruption in Indonesia can be done in various strategic ways, for example through the world of education, arts and culture, and activities that involve broad community participation.